Autophagy role(s) in response to oncogenes and DNA replication stress - Vanzo, Riccardo; Bartkova, Jirina; Merchut-Maya, Joanna Maria; Hall, Arnaldur; Bouchal, Jan; Dyrskjøt, Lars; Frankel, Lisa B; Gorgoulis, Vassilis; Maya-Mendoza, Apolinar; Jäättelä, Marja; Bartek, Jiri (Cell death and differentiation, 2020)
Autophagy is an evolutionarily conserved process that captures aberrant intracellular proteins and/or damaged organelles for delivery to lysosomes, with implications for cellular and organismal homeostasis, aging and diverse pathologies, including cancer. During cancer development, autophagy may play both tumour-supporting and tumour-suppressing roles. Any relationships of autophagy to the established oncogene-induced replication stress (RS) and the ensuing DNA damage response (DDR)-mediated anti-cancer barrier in early tumorigenesis remain to be elucidated. Here, assessing potential links between autophagy, RS and DDR, we found that autophagy is enhanced in both early and advanced stages of human urinary bladder and prostate tumorigenesis. Furthermore, a high-content, single-cell-level microscopy analysis of human cellular models exposed to diverse genotoxic insults showed that autophagy is enhanced in cells that experienced robust DNA damage, independently of the cell-cycle position. Oncogene- and drug-induced RS triggered first DDR and later autophagy. Unexpectedly, genetic inactivation of autophagy resulted in RS, despite cellular retention of functional mitochondria and normal ROS levels. Moreover, recovery from experimentally induced RS required autophagy to support DNA synthesis. Consistently, RS due to the absence of autophagy could be partly alleviated by exogenous supply of deoxynucleosides. Our results highlight the importance of autophagy for DNA synthesis, suggesting that autophagy may support cancer progression, at least in part, by facilitating tumour cell survival and fitness under replication stress, a feature shared by most malignancies. These findings have implications for better understanding of the role of autophagy in tumorigenesis, as well as for attempts to manipulate autophagy as an anti-tumour therapeutic strategy.
Keywords: replikace DNA; biologické modely; autofagie; Models, Biological; Stress, Physiological; kamptothecin; nádorové buněčné linie; Autophagy; Oncogenes; Camptothecin; Humans; autofagozomy; Cell Line, Tumor; fyziologický stres; Autophagosomes; onkogeny; lidé; DNA Replication